A new triterpenoid saponin from the stem bark of Pometia pinnata - Mohammad, Faryal Vali; Ahmad, Viqar Uddin; Noorwala, Mushtaq; Lajis, Md. Nordin (Natural Product Inc., 2010)
Phytochemical investigation of the stem bark of Pometia pinnata resulted in the isolation of a new triterpenoidal saponin. The structure of the new compound, pometin (1), was established as 3-O-[beta-D-glucopyranosyl-(1 --> 2)-beta-D-glucopyranosyl-(1 --> 3)-beta-D-glucopyranosyl]-oleanolic acid based on 1D and 2D-NMR analysis including COSY, 2D J-resolved, HMQC, HMBC correlations and chemical transformations.